2011
DOI: 10.1007/s00011-011-0325-6
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt signaling pathway is involved in the pathogenesis of ulcerative colitis

Abstract: The PI3K/Akt signal transduction pathway is involved in the regulation and release of pro-inflammatory cytokines such as TNF-α and plays an important role in the development and progression of UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 37 publications
6
78
0
Order By: Relevance
“…6). These observations with a preferential p110␣/␥ PI3K inhibitor complement earlier studies showing that 1) intravenous administration of small interfering RNA directed against the p85␣ subunit of PI3K markedly attenuates inflammatory changes associated with DSS-induced colitis (49); 2) intrarectal administration of small interfering RNA directed against the p85␣ subunit of PI3K significantly increases the survival of mice treated with DSS (29); and 3) wortmannin (an earliest broad-acting PI3K inhibitor) suppresses DSS-induced colitis (28). To the best of our knowledge, this is the first report of a preferential PI3K-␣/␥ inhibitor that not only blocks induced NF-B activation and consequent production/function of proinflammatory cytokines in human cells, but also attenuates experimental colitis when administered orally in a therapeutic regimen.…”
Section: Discussionsupporting
confidence: 65%
“…6). These observations with a preferential p110␣/␥ PI3K inhibitor complement earlier studies showing that 1) intravenous administration of small interfering RNA directed against the p85␣ subunit of PI3K markedly attenuates inflammatory changes associated with DSS-induced colitis (49); 2) intrarectal administration of small interfering RNA directed against the p85␣ subunit of PI3K significantly increases the survival of mice treated with DSS (29); and 3) wortmannin (an earliest broad-acting PI3K inhibitor) suppresses DSS-induced colitis (28). To the best of our knowledge, this is the first report of a preferential PI3K-␣/␥ inhibitor that not only blocks induced NF-B activation and consequent production/function of proinflammatory cytokines in human cells, but also attenuates experimental colitis when administered orally in a therapeutic regimen.…”
Section: Discussionsupporting
confidence: 65%
“…Recent studies have demonstrated that the imbalance of pro-inflammatory cytokines and anti-inflammatory cytokines are related to the pathogenic mechanisms of UC [24]. Activation of the PI3K/Akt and NF-jB signal transduction pathway facilitate the expression and secretion of pro-inflammatory cytokines which create imbalanced cytokine profiles [25]. In this study, kaempferol diets effectively down-regulated the colonic mRNA expression level of the major pro-inflammatory cytokines, e.g., TNF-a, IL-1b, and IL-6, which indicate that kaempferol plays a role in the cytokines production.…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal release of proinflammatory cytokines such as tumor necrosis factor alpha (TNF-a) and prostaglandin D2 are important mediators in the pathogenesis of UC. 4,5 In general, the medical treatment of UC starts with 5-aminosalicylic acid as the baseline medication, followed by steroids and immunomodulators. Moreover, to intensify the treatment, infliximab, calcineurin inhibitors (cyclosporine A and tacrolimus), or surgery may be considered as rescue therapy.…”
Section: Introduction Umentioning
confidence: 99%